Cardioprotective role of carvedilol in patients on chemotherapy: systematic review and meta-analysis of randomized clinical trials - Florio Legnani, Lucía (2018)
Objective: Cancer therapy may cause cardiovascular toxicity even after successful treatment. It is unknown the cardioprotective role of carvedilol in this setting. We evaluated the role of carvedilol for the prevention of left ventricular systolic dysfunction in chemotherapy patients. Materials and methods: A systematic review and meta-analysis of randomized clinical trials were performed through PubMed, Embase, Cochrane, SciELO and ClinicalTrials.gov, including trials that evaluated and compared the difference of left ventricular ejection fraction (pre- and post-chemotherapy) in patients with and without carvedilol treatment. The effect size was expressed as the standardized difference (d) and the mean difference between groups with 95 % confidence interval. Results: Nine thousand seven hundred forty-nine (9,749) manuscripts were screened. Four (4) studies consisting of a total of 343 adult patients, from which 86.9 % were females with normal left ventricular ejection fraction and no past history of heart failure, were included. The carvedilol group showed less –though not statistically significant– reduction of the left ventricular ejection fraction than the control group (d = -0.501 [-1.372, 0.371]; p = 0.260). The difference of the reduction in the left ventricular ejection fraction pre- and post-chemotherapy in both groups was -0.71 % [-1.88, 0.46]. However, left ventricular ejection fraction post-chemotherapy was higher in the carvedilol group (d = 0.361 [0.146, 0.575]; p = 0.006) and the effect size was 1.73 % [0.74, 2.72]. Conclusions: Monotherapy or combination therapy with carvedilol is associated with a higher left ventricular ejection fraction, but not with less reduction in the left ventricular ejection fraction post-chemotherapy. Long-term, larger and high-quality randomized clinical trials are required to determine the clinical implication of the use of carvedilol in patients under chemotherapy.